Cost-benefit analysis of a reliability model on water process system having two types of redundant subsystems - Rani, Sunita; Kumar, Rajeev (International Journal of Applied Mathematical Research, 2013)
In this paper a reliability model on a water system working in Panipat Thermal Plant, Panipat is considered. It was observed while visiting the plant that the system is consist of several redundant and non-redundant sub-systems where redundant sub-systems are of two types i.e. 1-out-of-2 (type-I) and 2-out-of-3 (type-II). On the occurrence of a minor fault in any subsystem the system goes to partial failure whereas on occurrence of a major fault in the non-redundant subsystem it completely fails. On partial failure of the system, the repairman available first inspects whether the fault is in redundant subsystem or in non-redundant subsystem and accordingly carries out the repair of the subsystem involved. Various measures of system effectiveness are obtained by using Markov processes and regenerative point technique. Using these measures the system is analysed in terms of its reliability and cost and various conclusions are drawn on the basis of the graphical studies.